A splice site mutation in the TSEN2 causes a new syndrome with craniofacial and central nervous system malformations, and atypical hemolytic uremic syndrome. Issue 3 (7th January 2022) - Canpolat, Nur; Liu, Dingxiao; Atayar, Emine; Saygili, Seha; Kara, Nazli Sila; Westfall, Trudi A.; Ding, Qiong; Brown, Bartley J.; Braun, Terry A.; Slusarski, Diane; Karli Oguz, Kader; Ozluk, Yasemin; et al.
Abstract: Recessive mutations in the genes encoding the four subunits of the tRNA splicing endonuclease complex ( TSEN54, TSEN34, TSEN15, and TSEN2 ) cause various forms of pontocerebellar hypoplasia, a disorder characterized by hypoplasia of the cerebellum and the pons, microcephaly, dysmorphisms, and other variable clinical features. Here, we report an intronic recessive founder variant in the gene TSEN2 that results in abnormal splicing of the mRNA of this gene, in six individuals from four consanguineous families affected with microcephaly, multiple craniofacial malformations, radiological abnormalities of the central nervous system, and cognitive retardation of variable severity. Remarkably, unlike patients with previously described mutations in the components of the TSEN complex, all the individuals that we report developed atypical hemolytic uremic syndrome (aHUS) with thrombotic microangiopathy, microangiopathic hemolytic anemia, thrombocytopenia, proteinuria, severe hypertension, and end‐stage kidney disease (ESKD) early in life. Bulk RNA sequencing of peripheral blood cells of four affected individuals revealed abnormal tRNA transcripts, indicating an alteration of the tRNA biogenesis. Morpholino‐mediated skipping of exon 10 of tsen2 in zebrafish produced phenotypes similar to human patients. Thus, we have identified a novel syndrome accompanied by aHUS suggesting the existence of a link between tRNA biology and vascular endothelium homeostasis, which we propose to name with the acronym TRACK syndrome ( T SEN2 R elated A typical hemolytic uremic syndrome, C raniofacial malformations, K idney failure). Abstract :